Tailored adaptation: Aligning social issue engagement with types of legitimacy challenges - Wu, Wenxin; Wang, Heli; Tong, Li; Zhang, Yanlong (Strategic Management Journal, 2025)
Abstract Research Summary Prior research generally suggests that addressing shareholder interests may come at the expense of non‐shareholding stakeholders. Our study challenges this notion by examining how shareholder interests, alongside those of other stakeholders, may align with social issue engagement. Specifically, we explore the relationship between legitimacy challenges (i.e., shareholder activism and social disapproval) and firm strategies in social issue engagement. We find that shareholder activism is positively associated with the materiality of social issue engagement, reflecting a firm's relative emphasis on material social issues over immaterial ones. Conversely, social disapproval is negatively associated with such emphasis. Furthermore, these relationships vary with investor relations officer engagement, the presence of social welfare nonprofits, and SASB standards promulgation. Our findings contribute to the literature on legitimacy management and social issue engagement. Managerial Summary Managing relationships with both shareholders and non‐shareholding stakeholders is complex amid a diverse landscape of social issues. Firms should be aware of the multifaceted nature of legitimacy challenges and tailor their response strategies accordingly. This study explores the challenges posed by shareholder activism and social disapproval, revealing that shareholder activism is positively related to a firm's relative emphasis on material social issues over immaterial ones, while social disapproval is negatively related to such emphasis. Furthermore, these dynamics are influenced by factors such as investor relations officer engagement, the presence of social welfare nonprofits, and the adoption of SASB standards. The study enhances the understanding of how firms navigate legitimacy challenges and strategically prioritize social issues to meet stakeholder expectations.